2020
DOI: 10.1016/j.cose.2019.101651
|View full text |Cite
|
Sign up to set email alerts
|

Risk as affect: The affect heuristic in cybersecurity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 76 publications
3
7
0
Order By: Relevance
“…A small and recent body of literature (for example: Lawson et al, 2016; Stacey et al, 2021; van Schaik et al, 2020) has begun to focus on the impact of emotion on cyber‐security. There has recently been a call for better research tools that are able to disentangle the relationship between emotion and cyber‐security (Renaud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A small and recent body of literature (for example: Lawson et al, 2016; Stacey et al, 2021; van Schaik et al, 2020) has begun to focus on the impact of emotion on cyber‐security. There has recently been a call for better research tools that are able to disentangle the relationship between emotion and cyber‐security (Renaud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, since the pandemic is quite dangerous, the individual's perception of the level of danger of the pandemic also influences their judgment and processing of information [44]. From another point of view, individuals who perceive a high risk will develop a certain level of anxiety and fear [49]. As suggested by the affect heuristic theory, decision makers' emotions affect their ability to process risk information, prompting the prospective entrepreneurs to make irrational information evaluations and thus influencing their decisions.…”
Section: Perceived Risk Moderates the Relationship Between Ei And Eamentioning
confidence: 99%
“…As Acquisti [22] pointed out, normative models do not properly explain privacy decisions, and "it is unrealistic to expect individual rationality in this context," as users mostly "resort to simple heuristics." However, there has been little investigation into the nature and specific role of heuristics in information security [16][17][18][19]. Over the years, several studies sporadically delve into the role of bounded rationality and heuristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite advances in various other fields [6,[11][12][13][14], fewer number of studies have investigated the role of heuristics in information security literature [15][16][17][18][19]. Many prior heuristics-related studies include research commentary, review, and call for research studies, which have suggested that heuristics may influence security decision making but have not empirically investigated their role [15,20].…”
Section: Introductionmentioning
confidence: 99%